Fairness in drug prices: do economists think differently from the public?. Issue 1 (4th December 2018) - Trujillo, Antonio J.; Karmarkar, Taruja; Alexander, Caleb; Padula, William; Greene, Jeremy; Anderson, Gerard
Abstract: Using dual-entitlement theory as the guide, we conducted a survey of economists from the National Bureau of Economic Research asking them a series of questions about the fairness of drug prices in the United States. Public opinion surveys have repeatedly shown that the public perceives drug prices to be unfair, but economists trained in laws of supply and demand may have different perceptions. Three hundred and ten senior economists responded to our survey. Forty-five percent agreed that drug prices were unfair when people, specifically low-income individuals, could not afford their prescription medications. Sixty-five percent oppose a dollar threshold, or upper limit, on drug prices. The economists recommend the most promising policy change would be to provide the government additional negotiating power and price controls would moderately impact investment in pharmaceutical research and development.